Nursing home residents attending the emergency department: clinical characteristics and outcomes. - O'Neill, Desmond; Coughlan, Tara; Kennelly, Sean; Briggs, Robert; Collins, Daniel (My University, 2013)
Nursing home (NH) residents represent the frailest group of older people, and providing gerontologically attuned care that addresses these frailties is often a challenge within the emergency department (ED). This study sought to prospectively profile acutely unwell NH residents in order to clarify some of the challenges of providing emergency care to this group. Over an 18-week period, we prospectively reviewed all NH residents presenting to the ED of an urban university teaching hospital. Relevant data were retrieved by direct physician review (as part of a comprehensive geriatric assessment in the ED), collateral history from NH staff and primary carers, and review of electronic records. There were 155 ED visits by 116 NH residents. Their mean age was 80.3 (±9.6) years. High pre-morbid levels of dependency were reflected by a mean Barthel Index of 34.1 (±20) and almost two-thirds had a pre-existing diagnosis of dementia. One-third of visits were during ‘normal’ working hours. Patients were reviewed by their regular NH doctor pre-transfer for 36% of visits. Using accepted international criteria, over half of the visits were deemed ‘potentially preventable’. Unwell NH residents have complex medical needs. The decision to refer these patients to the ED is often made by ‘out of hours’ general practitioners and their initial care in the ED is directed by physicians with limited experience in geriatric medicine. Most referrals to the ED are potentially preventable but this would require enhancements to the package of care available in NHs.
PUBLISHED
Keywords: Nursing home (NH) residents; Ageing; Neuroscience